A clinical study of C arm-guided selective spinal nerve block combined with low-temperature plasma radiofrequency ablation of dorsal root ganglion in the treatment of zoster-related neuralgia - Zhang, Zhen-Wu; Zhao, Yan; Du, Tian-Yi; Zhang, Juan; Wu, Qiong; Wang, Zhe-Yin (Frontiers in Neurology, 2023)
Background This study evaluated the analgesic efficacy and psychological response of low-temperature plasma ablation of dorsal root ganglion (DRG) combined with selective spinal nerve block in patients with acute or subacute zoster-related neuralgia (ZRN). Methods Totally 90 ZRN patients were randomly and evenly divided into three groups. Treatment was given to Group A using C arm-guided selective spinal nerve block (C-SSVB), Group B using C-SSVB and pulsed radiofrequency (PRF), and Group C using C-SSVB and low-temperature plasma ablation of the DRG. The outcomes were examined using the Visual Analog Scale (VAS). Anxiety and depression of patients were evaluated using the Self-rating Anxiety Scale (SAS) and Self-rating Depression Scale (SDS). Quality of life was assessed using the Pittsburgh Sleep Quality Index (PSQI) and postoperative Satisfaction scale. In addition, data on adverse events and medication usage rates were collected. Results The 90 patients were eligible for this study. The three treatments reduced VAS scores with no significant difference between groups A and B at the same time points; however, group B tended to have numerically lower VAS scores. Comparatively, group C had significantly reduced VAS scores on day 1 and 1 month after treatment compared with the other two groups. In terms of the decreasing SAS, SDS and PSQI scores, all the three treatments improved the anxiety, depression and sleep quality of the patients. In addition, significant alleviation in anxiety was found in group C compared with group A at all- time points. However, there was no statistically significant difference among the three groups in treatment-related adverse events that mainly focused on puncture pain at the surgical-site, skin numbness and medication usage rates. Conclusions C-SSVB and LTPRA of DRG will be considered as a promising treatment option for ZRN patients if those results can be confirmed after further validation.